2005
DOI: 10.1007/s00467-005-1892-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalciuria and recurrent urinary tract infections: incidence and symptoms in children over 5 years of age

Abstract: Hypercalciuria is an important and common risk factor in the formation of renal stones. In this study we evaluated the incidence and the clinical presentation of hypercalciuria in 75 children over 5 years of age with the diagnosis of recurrent urinary tract infection (UTI). We measured random urinary calcium/creatinine value (three times), 24-h urinary calcium excretion, serum calcium, phosphorus, electrolytes, blood gas, blood urea nitrogen and creatinine levels. Hypercalciuria was found in 32 patients (43%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 19 publications
1
31
0
13
Order By: Relevance
“…The prevalence of urolithiasis in the families of these patients has been reported between 34% and 59%. 17,18,31,32 In our study, there was a significant difference between the IHC and NC groups in terms of the rate of family history of urolithiasis. Furthermore, the rate of parental consanguinity was found to be higher in the IHC group.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…The prevalence of urolithiasis in the families of these patients has been reported between 34% and 59%. 17,18,31,32 In our study, there was a significant difference between the IHC and NC groups in terms of the rate of family history of urolithiasis. Furthermore, the rate of parental consanguinity was found to be higher in the IHC group.…”
Section: Discussionmentioning
confidence: 46%
“…In a study performed by Lopez et al, 18 the frequency of hematuria was reported to be 12% in patients with recurrent UTI and IHC. In another study conducted by Biyikli et al, 17 hematuria was reported as 35% in children with IHC and recurrent UTI, whereas this ratio was 33% in those without IHC. In our study, the frequency of hematuria was reported to be 16.7% in patients with IHC, and there was no significant difference with NC group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…72 Hypercalciuria was also found in 43% of children with recurrent urinary tract infection. 73 Therapy for bone fragility in childhood has been limited to conservative measures, such as optimizing calcium and vitamin D intake, even though adequate calcium and vitamin D intake may not be enough to treat osteoporosis, 74 particularly in patients with a high fracture risk. To date, no outcome study on the use of vitamin D has proven convincingly that this vitamin is insufficient for patients with a high fracture risk.…”
Section: Prevention and Non-pharmacological And Pharmacological Treatmentioning
confidence: 99%